Work Environment and Job Performance Variable as Factors Influencing Library Personnel Turnover Intentions in Private University Libraries in South-South, Nigeria - Odiachi, Rosemary Anwuli (Ghana Library Journal, 2022)
The study looked at work environment and job performance as factors influencing library personnel turnover intentions in private university libraries in Nigeria’s South-South region. The correlational survey design was used in the study. The study included 113 library personnel, including 39 professionals, 46 paraprofessionals, and 28 support staff. A questionnaire created by the researcher was used to collect data. The on-the-spot mode of data collection was used. A total of 103 copies of the 113 copies of the questionnaire were obtained, resulting in a 91.15 percent return rate. To analyze data derived from the research questions, descriptive statistics of Pearson Product Moment Correlational Coefficient (r) (PPMCC) were used. The findings of the study show that there is a high relationship (r = 64) between work environment and turnover intentions and a medium relationship (r = 0.41) between job performance and turnover intentions and a high relationship (r = 64) between motivation and turnover intentions of library personnel in private university libraries in South-South, Nigeria. The study recommends that private university managers should make the library working environment conducive by providing and making available amenities such as well-furnished offices with modern cabinets and furniture, air-conditioner fans, and Information and Communication Technologies (ICT). The private university library managers should ensure that library personnel who perform credibly, very well, and stand out in their job responsibilities are recognised, recommended, rewarded, and compensated monetarily and otherwise.